Analysis of international shipping emissions reduction policy and China’s participation - Liu, Huirong; Mao, Zhengkai; Li, Xiaohan (Frontiers in Marine Science, 2023)
In addressing climate change, the shipping industry, which is regarded as one sector that cannot be ignored in controlling greenhouse gas emissions, has become a key area of concern for the international community to achieve emissions reduction targets. The International Maritime Organization—the body that regulates international shipping—as well as the European Union and other international entities have adopted a series of emissions reduction policies, beginning a new era of shipping emissions reduction. In view of the urgency and complexity of this issue, the future policy direction of shipping emissions reduction and whether or not existing policies can achieve the emissions reduction targets have become the focus of attention in the global shipping industry. In addition, China’s dual identity as a shipping magnate and a developing country plays a crucial role in the development of shipping emissions reduction trends, and reducing shipping emissions is necessary for China to achieve the “double carbon” commitment. In view of the above, this study endeavours to compare the current major shipping emission reduction policies from the perspective of international law and the perspective of macro policies, and analyze the future direction of international shipping emissions reduction policy. At the same time, the study identify China as one of the key countries to influence future policy making and proposes the position and path for China's participation in international shipping emissions reduction, which provided valuable contributions for China to participate in accelerating energy transformation, exploring participation in the carbon emission market, and promoting international unified shipping policy.